Electronic participation through social media - Alarabiat, Ayman (2016)
It is widely acknowledge that many of e-Participation initiatives often attract wider audience and face serious limited citizens’ involvement. The use of social media has been seen as a hope to remedy such limitation. However, despite the recently adoption of social media the lack of citizens’ involvement in e-Participation initiatives still remains. This ongoing research paper aims at producing a general overview of e-Participation through social media. So far, the latest research works on such topic have been predominantly focused on a political context of e-Participation, where politicians-citizens interactions and activities are the central interest of the studies. Little existing studies investigate e-Participation in its own right in government context. The findings also reveal that the majority of e-Participation through social media initiatives are more informative than interactive, since few initiatives have been found that aim to considerably enhance citizen participation in policy decision making.